Deep biopsy via endoscopic submucosal dissection in upper gastrointestinal subepithelial tumors: a prospective study - Tae, Hye Jin; Lee, Hang Lak; Lee, Kang Nyeong; Jun, Dae Won; Lee, Oh Young; Han, Dong Soo; Yoon, Byung Chul; Choi, Ho Soon; Hahm, Joon Soo (Endoscopy, 2014)
Background and study aims: Preoperative pathological diagnosis may improve clinical management decisions in patients with upper gastrointestinal subepithelial tumors (SETs). The aims of this study were to evaluate the diagnostic yield of deep biopsy via an endoscopic submucosal dissection (ESD) technique, the complications associated with the procedure, and the impact on management of patients with upper gastrointestinal SETs.Patients and methods: A total of 68 patients with SETs in the stomach or esophagus were voluntarily assigned to two groups. One group underwent endoscopic ultrasound (EUS) and endoscopic deep biopsy using the ESD technique (40 patients), and the other group (28 patients) underwent surgical resection after EUS without obtaining preoperative pathological diagnosis, in accordance with accepted clinical management algorithms.Results: The diagnostic yield of deep biopsy was 90 % (36/40). The results of deep biopsy changed the treatment plans in 14/40 patients (35 %). One patient with lymphoepithelial carcinoma was scheduled for surgical resection, and 13 patients with benign SETs of diameter ≥ 2 cm avoided surgery. Of the 28 patients who underwent surgical resection without preoperative pathological diagnosis, 12 (42.9 %) were confirmed to have benign lesions. The mean procedure time for deep biopsy was 13.7 minutes. There were no procedure-related complications in the deep biopsy group. Conclusions: Deep biopsy by the ESD technique is a safe, high-yield, diagnostic method in patients with upper gastrointestinal SETs. Pathologic confirmation could improve clinical decision making in the management of patients with upper gastrointestinal SETs. Clinical trial registration: NCT 01993199